Impact of simulation-based anesthesiology training using an anesthetized porcine model for ultrasound-guided transversus abdominis plane block. Issue 3 (March 2020) - Park, Sang Jun; Kim, Hyun Joo; Yang, Hun-Mu; Yoon, Kyung Bong; Lee, Ki-Young; Ha, Taehoon; Jang, Hun; Kim, Shin Hyung
Objective: This study was performed to assess the impact of simulation-based training for ultrasound-guided transversus abdominis plane (TAP) block using anesthetized pigs. Methods: In this prospective study, 23 participating residents (10 in their second year, 13 in their third year) underwent simulation-based training for ultrasound-guided TAP block. The residents completed standard questionnaires comprising 10 multiple-choice questions regarding essential general knowledge of abdominal ultrasound and TAP block before and after the training session. On a 5-point Likert scale, they reported their levels of comfort with the use of ultrasound and block equipment, subject/operator positioning, proper block technique, image documentation, needle handling, anxiety, and their overall confidence with the procedure. Results: Compared with those before training, the comfort levels of the residents significantly improved for all measures except needle handling. The participants also indicated significantly reduced anxiety regarding performance of the TAP block technique. Conclusion: The use of anesthetized pigs in simulation-based training for ultrasound-guided TAP block improves procedural knowledge and confidence while reducing the associated anxiety in anesthesiology trainees.